Developments in multiple breath washout testing in children with cystic fibrosis. (3rd April 2017) - Saunders, Clare; Bayfield, Katie; Irving, Samantha; Short, Christopher; Bush, Andrew; Davies, Jane C.
Abstract: Background: Lung clearance index (LCI) is becoming recognized as an important addition in the monitoring of pediatric cystic fibrosis (CF). The non-invasive technique is easy to perform in all ages, reproducible and increasingly being used in clinical trials. There is interest in utilizing it within the clinic setting but its current use is mostly as a research tool. The procedure is highly dependent on skilled operators and a relaxed testing environment is key to obtaining good quality measurements. Conclusions: Standardization of LCI is part of an ongoing collaborative, multicenter process. This review describes the background to LCI, discusses technical issues and limitations and provides examples of its utility in clinical and research contexts.